Evaluation of Predictors of Response to Ovulation Induction Using Letrozole in Women with Polycystic Ovary Syndrome: A Prospective Cohort Study - Shanti Tholiya; Archana Kumari; Reeta Mahey; Mani Kalaivani; Hem Chandra Sati; Mona Sharma; Aarthi K. Jayraj; Neena Malhotra (Journal of Human Reproductive Sciences)
Background: Ovulation induction (OI) in patients with polycystic ovary syndrome (PCOS) remains challenging, and several biomarkers have been evaluated for their ability to predict ovulation. The predictive ability of candidate biomarkers, particularly with letrozole-based therapy in infertile PCOS women, remains inconclusive as it is yet to be evaluated in a prospective study. Aim: To assess the role of anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH), luteinising hormone (LH)/FSH ratio, testosterone and free androgen index (FAI) as predictors of ovarian response to letrozole-based OI therapy during OI cycles in infertile women with PCOS from North India. Settings and Design: A prospective cohort study was conducted in a tertiary care hospital in north India. Materials and Methods: The study enrolled 80 infertile women with PCOS, diagnosed according to the Rotterdam criteria. OI was conducted using letrozole with or without human menopausal gonadotropin. Baseline endocrine and metabolic parameters, including serum AMH, FSH, LH, testosterone and FAI levels, were measured using ELISA or chemiluminescence methods on day 2 of the menstrual cycle. Follicular response to OI was monitored by transvaginal ultrasonography. Statistical Analysis Used: Descriptive and inferential statistical analyses were conducted, including Mann–Whitney, Kruskal–Wallis, Independent t-test, analysis of variance, Fisher’s exact test and receiver operating characteristic curve analysis. Data were processed using Microsoft Excel and analysed with SPSS software, version 25.0. P < 0.05 was considered statistically significant. Results: Of 80 women enrolled, 74 responded to letrozole-based OI, while six were non-responders. Body mass index (BMI), serum testosterone and pre-treatment AMH levels significantly correlated with follicular response, with higher values linked to reduced responsiveness. The likelihood ratio+ (95% confidence interval) was 3.32 (2.45–5.06) for AMH, 1.97 (1.03–3.78) for BMI and 1.93 (1.22–3.08) for testosterone. The odds ratio for AMH was 2.88 (1.01–8.21) and 1.25 (1.02–1.53) for BMI. An AMH cut-off of ≤16.43 ng/mL predicted ovarian response with an AUC of 0.88. Conclusions: Pre-treatment AMH levels, along with BMI and serum testosterone, are significant predictors of ovarian response to letrozole-based OI in infertile women with PCOS.